Media Health The Personal in Public Stories - Nathalie Hyde-Clarke (Scandinavian University Press (Universitetsforlaget), 2020)
This edited volume explores how journalists and other media actors apply personalized frames and narratives, both visual and verbal, in representing and conveying health issues. Today's feature journalism in weekend editions of major newspapers frequently communicate very personal experiences, often visualized through a series of portrayed people's process of growing up, accompanied by images gathered from private photo albums. An expanding TV genre follows the journalist as a protagonist trying to come to terms with e.g. their own body, sexual orientation or experiences of suicide in close relations. In social media, journalists present their news even more subjectively and interpretatively compared to legacy media. Stories on lifestyle diseases, mental health or infectious diseases are unavoidably connected to broader practices of health policies, workplace strategies and legislation. Instead of either celebrating or deploring the tendency towards more personalized health journalism, the contributions to this volume explore how individuals and exemplars are represented in journalistic media, and what these representations imply about people's understanding of - and participation in - important health issues in society. The data gathered and examined in this volume are from the Nordic countries. The Nordic countries represent an interesting case study in media regulation globally, combining robust protections of press freedom with a significant level of regulation - reflecting the assumption that media are a social institution and not simply a private business. The Nordic countries are characterized by a high level of media distribution and consumption, both when it comes to legacy and social media. In this region, news media are also known to be innovative and resourceful, paving the way for new genres and formats. Another important factor is the high level of public health systems and social security legislation in the Nordic countries, which also makes the Nordic countries an interesting field of study.